2022
DOI: 10.1038/s41420-022-01148-5
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial RNA polymerase POLRMT promotes skin squamous cell carcinoma cell growth

Abstract: RNA polymerase mitochondrial (POLRMT) expression and the potential biological functions in skin squamous cell carcinoma (SCC) were explored. We showed that POLRMT is significantly elevated in skin SCC. Genetic depletion of POLRMT, using shRNA-induced knockdown or CRISPR/Cas9-mediated knockout (KO), resulted in profound anti-skin SCC cell activity. In patient-derived primary skin SCC cells or immortalized lines (A431 and SCC-9), POLRMT shRNA or KO potently suppressed mitochondrial DNA (mtDNA) transcription and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Besides the role of POLRMT in NSCLC, recently published studies have revealed the protumoral role of POLRMT in skin squamous cell carcinoma, osteosarcoma, acute myeloid leukemia, and breast cancer. Considering the role of POLRMT in mtDNA transcription, these studies assessed the transcripts of mtDNA genes (e.g., mitochondrial mRNA levels, subunits of respiratory chain complexes, and S6 phosphorylation), and found that the expression of these genes decreased with decreasing POLRMT expression 5,6,7,10 . However, these studies did not assess whether POLRMT was involved in any biological pathway linked to cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the role of POLRMT in NSCLC, recently published studies have revealed the protumoral role of POLRMT in skin squamous cell carcinoma, osteosarcoma, acute myeloid leukemia, and breast cancer. Considering the role of POLRMT in mtDNA transcription, these studies assessed the transcripts of mtDNA genes (e.g., mitochondrial mRNA levels, subunits of respiratory chain complexes, and S6 phosphorylation), and found that the expression of these genes decreased with decreasing POLRMT expression 5,6,7,10 . However, these studies did not assess whether POLRMT was involved in any biological pathway linked to cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of POLRMT in mtDNA transcription, these studies assessed the transcripts of mtDNA genes (e.g., mitochondrial mRNA levels, subunits of respiratory chain complexes, and S6 phosphorylation), and found that the expression of these genes decreased with decreasing POLRMT expression. 5,6,7,10 However, these studies did not assess whether POLRMT was involved in any biological pathway linked to cancer development. Through GSEA, we found that high-level expression of POLRMT was linked to MYC targets and Wnt/beta-catenin signaling, both of which had a role in lung cancer cell processes and proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial transcription dysregulation has been implicated in various diseases [ 35 39 ], including cancer [ 9 , 40 – 45 ]. In cancer cells, alterations in mitochondrial transcription can contribute to tumor development and progression [ 9 , 40 , 41 ]. Dysregulated mitochondrial transcription can result in aberrant expression of mitochondrial genes involved in energy production, apoptosis, and other cellular processes [ 33 , 46 48 ].…”
Section: Dysregulation Of Mitochondrial Transcription Affects Tumor P...mentioning
confidence: 99%
“…POLRMT is a core component of the mitochondrial transcription machinery and is closely associated with tumor progression. Studies have shown that increased expression of POLRMT is observed in lung cancer [ 9 ], osteosarcoma [ 10 ], squamous cell carcinoma [ 41 ], endometrial cancer [ 40 ], and acute myeloid leukemia [ 77 , 78 ], and it can promote tumor cell proliferation, invasion, and migration abilities. The high expression of POLRMT is directly associated with poor prognosis in cancer patients [ 9 , 41 , 79 ].…”
Section: Dysregulation Of Mitochondrial Transcription Affects Tumor P...mentioning
confidence: 99%